The Effect of Civic Education Learning According to Students: Tadris English Students - Amri, Anisa Nurul; Oscar, Scherschligt; Kathryn, Morse (Yayasan Pendidikan Islam Daarut Thufulah, 2023)
Background. In realizing the national goals of the Indonesian nation, one way is to provide civic education which is a government effort in order to provide knowledge for the younger generation, especially students, to be able to carry out future generations as a generation responsible for the state and nation of Indonesia Purpose. The research objective of civics lessons is one of the compulsory subjects that contains teaching about the sense of nationalism and the moral values of the nation that we have gotten since we were in elementary school to the senior high school level. Method. This research aims to find out the opinions and views of students about the purpose and influence of civics lessons, especially for English Department students Results. This article uses a quantitative method which conducts a survey using a form to a number of participants and from the results of the survey obtained various opinions and views of Tadris English students at Institut Agama Islam Negeri Batusangkar about the purpose and influence of civics lessons for them, as well as their opinions if civics lessons are abolished. Conclusion. Will it have an impact on young people, especially students of Tadris English, Institut Agama Islam Negeri Batusangkar.